Modified Glomerular Filtration Rate-Estimating Equations Developed in Asiatic Population for Chinese Patients with Type 2 Diabetes - Xun Liu; Xilian Qiu; Chenggang Shi; Hui Huang; Jianhua Huang; Ming Li; Tanqi Lou (International Journal of Endocrinology)
Objectives. To evaluate eight modified equations developed in Asiatic populations in type 2 diabetic patients in China. Methods. A total of 209 Chinese patients with type 2 diabetes were recruited. Using the technetium—99m diethylenetriaminepentaacetic acid—glomerular filtration rate (GFR) to act as the reference, comparisons of their efficiency to estimate GFR in the subjects were made between various equations. Results. Median of difference of the Chinese equation 1 was the lowest (median of difference, 0.51 mL/min/1.73 m2). Median percent of absolute difference of the Chinese equation 2 was less than those of the other equations (26.97 versus ranged from 32.54 to 37.61 mL/min/1.73 m2, [P<0.001 for all]). Precision of the simplified reexpressed MDRD equation was the best (92.9 mL/min/1.73 m2). Accuracies of the Chinese equation 2 were greater (P<0.05 for all). There was also an improvement in chronic kidney disease (CKD) stage misclassification of the Chinese equation 2 (55.0 versus ranged from 61.2 to 64.6%, [P<0.001 for all]). However, the 30% accuracies of all the equations were less than 70%. Conclusions. Our study highlighted a limitation in the use of the above equations in the majority of Chinese diabetic subjects. A better equation is needed in order to give an accurate estimation of GFR in type 2 diabetic patients in China.